(3s(3)/11-5(t))^2 s=2 t=5
First you need to do this question orderly, so solve the number on the parentheses and then square them.
3s(3)=9s so (9s/11-5t)^2. There are two options. One you can square this equation and then put number on. The second you can put number on this equation and square the number on the parentheses.( the second way is much easier!)
put s=2 t=5 into this equation 9*2/11-5*5 = 18/(-14); Simplifeid this equation will get 9/(-7)
than square them (9/(-7))^2= 9^2/(-7)^2 = 81/49
The answer is 81/49